Some Non-Cognitive Factors as Correlates of Senior Secondary School Students’ Achievement in Mathematics - Badru, Ademola K. (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This study investigated some non-cognitive factors as correlates of senior secondary (SS) students’ achievement in mathematics in Ogun state. It adopted the non-experimental research design with two research questions raised. A sampling proportion to size was employed in selecting 26 SS from 254 schools in the state. An arm of intact class SS 2 students was selected from each school. Purposive sampling technique was used to select all the SSS 2 mathematics teachers. TQ; MAT; SQ; and PCEOS were developed, validated and their reliability coefficient values were 0.89; 0.75; 0.91; and 0.85 respectively. Data analyzed used was Multiple Regression statistical analysis. The findings revealed that the combinations of the independent variables accounted for 3.2% of the total variance observed in the students’ achievement in mathematics and significant. Hence, it is recommended that there should be frequent school inspection coupled with the teachers’ welfare, students’ achievement in mathematics would be improved. Key words:  Students’ mobility , Frequency of Inspection, Teachers’ job satisfaction, Classroom Environment Observation and achievement